Evaluating asset pricing anomalies: evidence from Latin America (2024)
We analyze the significance of 51 asset pricing anomalies in Latin America. We examine economic significance via portfolio simulations that dilute the effect of microcaps. To avoid reporting false discoveries, we employ a multiple hypothesis testing framework. Few anomalies are economically significant. Expanding the holding periods for long-short anomaly portfolios points out to the same direction. Anomalies are seldom significant when testing for statistical significance and tend to be more prevalent in small rather than in large stocks. However, their presence is not widespread. Thus, many anomalies in the extant literature do not survive out-of-sample scrutiny in this region.